Normal inter-limb differences during the straight leg raise neurodynamic test: a cross sectional study - Boyd, Benjamin S (BioMed Central, 2012)
BACKGROUND: The straight leg raise (SLR) neurodynamic test is commonly used to examine the sensitivity of the lower quarter nervous system to movement. Range of motion during the SLR varies considerably, due to factors such as age, sex and activity level. Knowing intra-individual, inter-limb differences may provide a normative measure that is not influenced by such demographic characteristics. This study aimed to determine normal asymmetries between limbs in healthy, asymptomatic individuals during SLR testing and the relationship of various demographic characteristics. METHODS: The limb elevation angle was measured using an inclinometer during SLR neurodynamic testing that involved pre-positioning the ankle in plantar flexion (PF/SLR) and neutral dorsiflexion (DF/SLR). Phase 1 of the study included 20 participants where the ankle was positioned using an ankle brace replicating research testing conditions. Phase 2 included 20 additional participants where the ankle was manually positioned to replicate clinical testing conditions. RESULTS: The group average range of motion during PF/SLR was 57.1 degrees (SD: 16.8 degrees) on the left and 56.7 degrees (SD: 17.2 degrees) on the right while during DF/SLR the group average was 48.5 degrees (SD: 16.1 degrees) on the left and 48.9 degrees (SD: 16.4 degrees) on the right. The range of motion during SLR was moderately correlated to weight (−0.40 to −0.52), body mass index (−0.41 to −0.52), sex (0.40 to 0.42) and self-reported activity level (0.50 to 0.57). Intra-individual differences between limbs for range of motion during PF/SLR averaged 5.0 degrees (SD: 3.5 degrees) (95% CI: 3.8 degrees, 6.1 degrees) and during DF/SLR averaged 4.1 degrees (SD: 3.2 degrees) (95% CI: 3.1 degrees, 5.1 degrees) but were not correlated with any demographic characteristic. There were no significant differences between Phase 1 and Phase 2. CONCLUSIONS: Overall range of motion during SLR was related to sex, weight, BMI and activity level, which is likely reflected in the high variability documented. We can be 95% confident that inter-limb differences during SLR neurodynamic testing fall below 11 degrees in 90% of the general population of healthy individuals. In addition, inter-limb differences were not affected by demographic factors and thus may be a more valuable comparison for test interpretation.